Dampak Pandemi COVID-19 terhadap Kinerja Nilai Ekspor Pertanian Indonesia - Achmad Subchiandi Maulana; Agustinus Nubatonis (Fakultas Pertanian, Universitas Timor, 2020)
The coronavirus pandemic has put the world in a state of crisis, both a health crisis and an economic crisis. As a result of this virus, trade between countries is hampered, due to a lockdown (large-scale social restrictions) which results in slow economic growth. Export is one of the international trade activities carried out by Indonesia. The agricultural sector contributes 2.3% of Indonesia's total exports, however, the agricultural sector is a sector that has survived a crisis. Seeing the situation in 2020, which has seen the COVID-19 pandemic in the last few months, it is interesting to observe whether the global crisis caused by COVID-19 has made a significant change in the performance of the export value of Indonesian agricultural products. The data used are monthly data analyzed using multiple linear regression, with the dependent variable being the value of Indonesian agricultural exports, while the independent variables are national gross domestic income, the exchange rate of the rupiah against the United States dollar, the volume of Indonesian exports, the volume of Indonesian agricultural exports, and COVID -19 as a dummy variable. The result is, the variables that have a significant effect on the value of Indonesian agricultural exports are the volume of Indonesian exports and the volume of Indonesian agricultural exports, while other variables do not have a significant effect.